TINJAUAN YURIDIS TERHADAP KEPASTIAN HUKUM AKTA PERJANJIAN JUAL BELI YANG OBJEKNYA DIJADIKAN JAMINAN DI BANK - Tumpak Siregar; Jaminuddin Marbun; Syawal Amry Siregar (JURNAL RETENTUM, 2020)
An agreement is an act in which one or more people bind themselves to one or more other people and can create a relationship in law which consists of one or more obligations. One of the many agreements is the sale and purchase agreement. The sale and purchase agreement is usually made before the parties enter into a sale and purchase agreement. The sale and purchase agreement is an obligatory agreement, namely an agreement that arises only by means of an agreement but has not resulted in a transfer of rights. A new transfer of rights will occur when a sale and purchase agreement is a material agreement. Binding and buying and selling of land rights objects that are still bound by bank guarantees still often occur in people's lives. This raises the question whether the agreement is valid or not and what the legal consequences are if the agreement is made? This research uses a research method in the form of juridical-normative research, While the data analysis method used by the author is a qualitative method and the data collection tools used are document studies or library materials. The result of the writing of this thesis is that the Sale and Purchase Agreement made in relation to objects that are still bound by bank guarantees is valid, but in the agreement it must be written clearly regarding the actual condition of the object of sale and purchase and its arrangements if it turns out that the object of sale and purchase is still bound by guarantee.